Innovations for sustainable lifestyles – an agent based model approach - Allen, Peter M.; Robinson, Marguerite; Butans, Eugene; Varga, Liz (Springer, 2018)
An important aspect of any scientific approach to sustainability must be methods by which the impacts of possible innovations can be assessed. Clearly, we need to make massive changes in our lifestyles if we are to get anywhere near ‘sustainability’. In this paper, an ‘agent-based model’ is developed which for this initial presentation explores probable impacts on household consumption and emissions of possible innovations. The model randomly picks a large number (here 10,000, but it can be much larger) of households from four different countries and calculates the effects resulting from the adoption of specific innovations. The ‘lifestyle’ of the households within the area studied is divided into four different ‘domains’. These are living, food, mobility and energy. Innovations are launched in the four different domains and the model shows the overall effects on the total input requirements (materials, energy, etc.), the household and food wastes and the CO2 emissions, showing how far the system moves towards sustainability. By using the sustainability criteria of 8000 kg ‘input material’ per year per individual developed by the Wuppertal Institute (Lettenmeier et al. in Resources 3:488–515, 2014, https://doi.org/10.3390/resources3030488, http://www.mdpi.com/journal/resources, ISSN 2079-9276), we can calculate how far the nation or region is from sustainability after adopting possible innovations. This is a measure of the total inputs required per individual per year. It allows us to show that for different countries, with widely different climates (e.g. Finland and Spain), different household innovations would have a greater or lesser impact on attaining ‘sustainable lifestyles’. The model does not pretend to develop a full simulation of each system, including the ecosystem, type of economy, etc., but does look at the effect an innovation in one household domain will have on all four domains, thereby providing information that can improve current decisions. It also demonstrates that, although ‘households’ can do much to improve the situation by reducing their demand for energy and materials, some actions at a national/regional level will be required to achieve sustainability. For example, sustainability will require an end to the use of fossil fuels for transportation and a switch to ‘clean’ electrical power generation from renewables and nuclear sources. Without this change, these countries will find it impossible to reach a sustainable lifestyle.
Keywords: Sustainable consumption; Emissions; Household innovations; Comparing countries